Agroextractivism in Argentina environmental health, scientific agendas, and socioecological crisis - Gargano, Cecilia (2023)
I will argue that agro-extractivism in Argentina is a major contributor to thesocioecological crisis and a threat to public health, and that it is necessary to promoteagroecology as an alternative model. In the absence of official statistics on the quantitiesof pesticides used in Argentina, we maintain that it is necessary to promote researchthat documents the environmental and health impacts of this agriculture. Furthermore,expanding state capacities for research and development in the fields of environmental healthand agroecology can be a strategy to promote the transformation of current production andconsumption patterns.